A new Version of High Stability Output 12-Bit Tracking Analog to Digital Converter - Elmaleeh, Mohammed A. A.; Ahmed, Hassan Y. (Gezira Journal of Engineering and Applied Sciences; مجلد 8 عدد 1 (2013), 2013)
In this paper a 12-bit tracking analog-to-digital converter (ADC) is designed and its performance is verified. It continuously tests the analog input signal and makes correction when necessary. The resulting digital equivalent of the analog input signal is continuously updated. The least significant bit (LSB) of this converter jumps up and down to track the analog input and this causes the final output to be unstable. To overcome the problem of instability in the digital output the 12-bit tracking ADC is modified by introducing the test bit B0. The test bit is designed to have a voltage equals to that of the LSB. It always sets or resets in tracking the analog value. Using this technique the digital output B1 to B12 of the converter is maintained stable. Test and measurements are performed in the converter circuit to demonstrate the practicality of this version.